The Impact of the Drastic Increase in Fuel Oil (Bbm) Prices - Bilqis Farikha Rizki Al Fajrin; Aziziyah Zahra Jinan; Putri Syahfitri Auliyah; Annisa Fitri Wulandari; Nurma Tambunan (International Journal Labs, 2023)
Fuel Oil (BBM) is a commodity that plays a vital role in all economic activities. The direct impact of this change in oil prices is a change in operating costs that results in the level of profit of direct investment activities occurring. In simple terms, the purpose of investing is to maximize prosperity through the maximization of profits, and investors always try to invest in efficient and safe investments. The increase in fuel prices not only increases the burden on small communities in general but also for the business world in particular. The surge in the price of Mintak Fuel (BBM) is considered to have a real effect on economic conditions in Indonesia. High oil prices turned out to be unfavorable to the economy of any country in Asia, including Indonesia. The increase in fuel prices in Indonesia is not only caused by the high increase in world oil prices, but also due to the domestic undersupply when compared to its demand. The amount of fuel subsidies such as in Indonesia, which can drain the state budget, is also considered as an excuse for the government to increase fuel prices in the country. The impact on various industrial sectors can lead to high production and operating costs. Moreover, of course, this increase in fuel prices will also have exponential implications for Indonesia's macroeconomic fundamentals.